1412 Sustainable farm families across the globe– the most important part of any farm is a healthy farm family. (24th April 2018) - Brumby, Susan; Hatherell, Tracey; Jensen, Jordan; Nelson, Laura
Abstract : Background: Farmers across the globe have increased risks – accident, injury, cardiovascular disease, diabetes, suicide and zoonosis. They also face difficulties accessing expertise exacerbated by large distances and lack of transport. The Sustainable Farm Families (SFF) program commenced in Australia in 2003 and has delivered 151 programs to over 2500 Australian farm men and women. In 2014, SFF commenced in Alberta, Canada and over 400 farmers have participated including 17 Hutterite communities. Each SFF program consists of 3 workshops, over 4 days, approximately 6–12 months apart. Methods: SFF is a multifaceted health program, developed specifically for the agricultural context. Each workshop is facilitated by trained SFF nurses and an agricultural facilitator. At the beginning of each workshop a full health assessment is gathered—anthropometric measures, lipid studies, glucose, blood pressure, psychosocial distress, waist measurement and% body fat. Health and safety behaviours are also reviewed. Education sessions on CVD, diabetes, stress, farm safety, anxiety, depression, diet and nutrition, respiratory conditions, pesticides, physical activity, men's health and women's health are devliered. Participants were >18 years, spoke English and were farming. Diabetes risk was assessed by the validated AUSDRISK or CANRISK tool and psychosocial distress using the Kessler K10. Results: More men than women participated showing that farmers are interested in their health, wellbeing and safety. 'Can't take care of the farm if you don't take care of yourself.' This presentation will discuss the baseline results from Australia and Canada. Where longitudinal data is available it will be discussed. In Australia, the results showed that the more risk factors you had when you began the SFF program the better you did, including reducing your risk factors. Conclusion: Both the Australian and Canadian program have been positively and extensively independently evaluated. The SFF program has been successfully repeated and transferred to Alberta, Canada, saving lives and saving money across the globe.